Surprise as a winter hunting strategy in Sparrowhawks Accipiter nisus, Peregrines Falco peregrinus and Merlins E columbarius - Cresswell, Will (Ibis, 1996)
Sparrowhawks Accipiter nisus, Peregrines Falco peregrinus and Merlins Falco columbarius were studied hunting Redshanks Tringa totanus, Dunlins Calidris alpina and Skylarks Alauda arvensis over three winters on a small Scottish estuary. Most Sparrowhawk and Merlin hunts consisted of a single attack (mean = 1.0 and 1.1, respectively), whereas Peregrine hunts often consisted of several attacks (mean = 1.8). Most hunts were short (<1 min), but Peregrine and Merlin hunts occasionally lasted over 5 min. In general, all three raptor species attacked by surprise, although Peregrines were more likely to make nonsurprise attacks. Prey attacked were usually initially very close to the raptor (<100 m); Peregrines attacked prey most often at long distances (>500 m). Chase lengths were mostly <5 second in length, although Peregrines, and particularly Merlins hunting Skylarks, often chased for several minutes. Peregrines attacked most prey in flight from flight, while Merlins and Sparrowhawks attacked birds on the ground with a flight from a perch. All three raptor species preferentially attacked larger Dunlin flocks, but Peregrines also favoured single birds. Capture rates of Redshanks and Dunlins were similar for the three raptor species (C. 10%), but for Skylarks, capture rate by Merlins was much higher (12%) than fay Sparrowhawks (3%) or Peregrines (0%). Capture rates were highest when raptors attacked by surprise, particularly for a Peregrine hunting in the first minute of arrival on the study site if no Peregrines had been hunting there for the previous hour (16% success for the first minute compared with 2% in subsequent minutes). Sparrowhawks were more successful when attacking small rather than large Dunlin flocks. The use of short surprise attacks interspersed with long periods of inactivity was common to the three raptor species and was interpreted as a strategy to minimize the amount of energy and risk involved in hunting during the nohbreeding season.